The effect of students' pre-admission performance on post-admission performance (2008)
This study uses canonical correlation analysis to investigate the effect of pre-admission performance (performance in SSCE/GCE and JAMB) on the post-admission performance (performance in 1OOlevel to 400 Level). The study population comprised of a set of students that were admitted in the same year in the department of computer science. University of Ibadan, Nigeria. The students’ SSCE/GC, JAMB. 100 Level to 400 level results were studied. The result shows that students ' pre-admission performance are highly correlated with their 100 level to 300 level, but uncorrelated with 400 level result. This may due to: complexity of the course as they are moving higher, effect of the project work. Strike, riot, lack of relevant textbooks, social activities. etc. This study then recommends that the University should introduce or assign level advisers to advice the students; they should ensure that they provide relevant textbooks to the library for the students.